Understanding the dynamics of phosphorus sorption in acidic soil amended with cocoa pod husk biochar - Neenu, S.; Gopal, Murali; Gupta, Alka; Bhat, Ravi; Apshara, S. Elain (Journal of Plantation Crops, 2023)
Cocoa pod husks (CPH) generated from cocoa gardens, after separation of beans from cocoa pods, were converted to biochar through pyrolysis. Though biochar itself is a source of many vital nutrients, it has got high capacity for nutrient sorption, much more than natural organic matter, by some estimates even 10 to 100 times. In soils, phosphorus exists mostly in organic and inorganic forms and many times become a limiting nutrient in acidic and alkaline soils because of adsorption, precipitation and complexation. Hence, better understanding of phosphorus sorption dynamics in soil is a key to know the bioavailability of P in a soil. In this study, an attempt was made to examine the P sorption vis-à-vis desorption properties when cocoa pod husk biochar is applied in an acidic soil with three diﬀerent levels of phosphorus availability. The biochar was applied @ 0, 5, 10, 20 and 40 g kg--1 to the acidic field soils which received inorganic fertilizer with and without organics and also unfertilized soils. Phosphorus retention and release was studied by fitting the equilibrium solution and sorbed concentrations of P by adsorption isotherms. The results showed that in all the soil biochar incubation treatments, increased biochar addition led to an increase in the soil available P and the P activation coeﬃcient. In the sorption-desorption study, it was found that phosphorus sorption increased with increasing rates of biochar application. The addition of biochar at 20 g kg-1 and 40 g kg-1 increased the equilibrium solution P concentration and increased available P as compared to lower doses of biochar. Also, fertilized soils sorbed more phosphorus (323.25 – 995.27 mg kg-1) than un-fertilized soils (347.25 - 805.47 mg kg-1) @ 0–40 g kg-1 biochar. All the treatments fitted satisfactorily with Langmuir equation (r2 = 0.96–0.99, P = 0.01) and Freundlich equation (r2 = 0.87–0.99, P = 0.01). In this paper, we explain the phosphorus adsorption features using Langmuir equation as the main isotherm. The conclusion drawn from this study was that the addition of CPH biochar could alter the P availability, which is directly related to the phosphorus sorption dynamics of the soil.